Environmental technology expertise of growing winter wheat on agrochemical and hygienic indicators of podzolized dark gray soil - Тогачинська, О. В.; Тимощук, Т. М. (Scientific Progress & Innovations, 2017)
We explicated results of the ecological examination of technologies for growing winter wheat in the Northern Forest-Steppe on the indicators of fertility and the effect on the migration of heavy metals in the genetic horizons of dark-gray podzolized soil. According to the results of environmental assessment, it is established that for the introduction of technologies in production, it is necessary to improve certain technological operations.